Instructional Materials of Quadratic Equations for 10th Grade Indonesia Students: Combined Round Robin-Cooperative Learning and Problem Posing - Ahmad Isroil (FKIP, Universitas Billfath Lamongan, 2020)
The purpose of this research is to describe the process of developing and producing effective learning tools for teaching quadratic equations in 10th grade by applying the Round Robin type of cooperative learning through posing problems, as well as to describe the effectiveness of the learning process itself. The problem posing approach allows students to utilize this knowledge when they encounter problems related to the materials being thought. The subjects of this research one 10th grade teacher and 10th grade students. The design of this study uses Kemp’s model of research and development (2011). The developed learning tools consists of: (1) lesson plans, (2) student’s worksheets, and (3) an achievement test. Based on descriptive analyses of the trial session, results show the lesson plan utilized was appropriate because it was: (1) valid; (2) practical; (3) effective. Based on descriptive results, the implementation session was also deemed effective. This conclusion is based on the conditions which indicate that the teacher’s ability to organize learning was effective, the students were active during learning process, the students responded positively to the learning process, and over 80% of the students achieved grades of 70 or higher.